The Supposed Necessity of the Legal Tender Paper - Barrett, Don C. (Quarterly Journal of Economics, 1902)
Journal Article The Supposed Necessity of the Legal Tender Paper Get access Don C. Barrett Don C. Barrett Haverford College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 16, Issue 3, May 1902, Pages 323–354, https://doi.org/10.2307/1881981 Published: 01 May 1902